Cold mix asphalt made with bitumen emulsion capsules - Alenezi, Thamer (2019)
Numerous studies have identified the benefits of cold mix asphalt (CMA) made of bitumen emulsion, compared to hot mix asphalt (HMA) made with bitumen. When CMA made with bitumen emulsion is used, more than 95% of the energy can be saved during its production. Also, heating is not required while mixing and compacting the CMA. However, emulsion mixes are used in the United Kingdom mainly for surface treatments due to weak early life strength, high air voids and long curing times. This present study investigates the performance of cold mix asphalt made with bitumen emulsion capsules. The initial objective of the research is to produce bitumen emulsion capsules with minimum water content, then mix the aggregates and bitumen emulsion capsules, followed by compaction at ambient temperature to provide enhanced mechanical properties as compared to conventional CMA made of bitumen emulsion. The bitumen emulsion capsules were produced by bitumen emulsion droplets coated by a shell made with calcium-alginate (Ca-alginate). Then the bitumen emulsion capsules were mixed with aggregates and compacted at ambient temperature. The research was undertaken to evaluate the effect of compaction energy, different cement contents, curing times and binder types on the mechanical properties of cold mix asphalt made with bitumen emulsion capsules. This research revealed that the mechanical properties of cold mix asphalt made with bitumen emulsion capsules increase with the increase of compaction energy. Moreover, the mechanical properties of cold mix asphalt made with bitumen emulsion capsules increased with curing time. The study also revealed that Ca-alginate was, itself, an effective binder type that can hold aggregates together resulting in better mechanical properties of mixtures. Thus, it was concluded that a cold mix pavement material made with Ca-alginate binder is a novel material for pavements with potential to be an alternative for conventional cold mix asphalt made with bitumen emulsion.